Conservation Agriculture Technologies Increase Productivity and Profitability of Cereal Based Farming System in Eastern Plains of Nepal - Pokharel, D; Jha, R. K.; Tiwari, T. P.; Ghatala, M. K.; Shrestha, H. K.; Panday, D. (Journal of Agriculture and Environment, 2019)
Available with full text.